Misoprostol administered sublingually at a dose of 12.5 μg versus vaginally at a dose of 25 μg for the induction of full-term labor: a randomized controlled trial - Daniele S. M. B. Gattás; Melania M. R. de Amorim; Francisco E. L. Feitosa; José R. da Silva-Junior; Lívia C. G. Ribeiro; Gustavo F. A. Souza; Alex S. R. Souza (BMC, 2020)
Abstract Background Labor induction is defined as any procedure that stimulates uterine contractions before labor begins spontaneously. The vaginal and oral routes of administration of misoprostol are those most used for the induction of labor in routine practice, with the recommended dose being 25 μg. Nevertheless, the sublingual route may reduce the number of vaginal examinations required, increasing patient comfort and lowering the risk of maternal and fetal infection. Based on a previous systematic review, the objective of this study was to compare the frequency of tachysystole as the main outcome measure when misoprostol is administered sublingually at the dose of 12.5 μg versus vaginally at a dose of 25 μg to induce labor in a full-term pregnancy with a live fetus. Methods A randomized, placebo-controlled, triple-blind clinical trial was conducted at two maternity hospitals in northeastern Brazil. Two hundred patients with a full-term pregnancy, a live fetus, Bishop score ≤ 6 and an indication for induction of labor were included. Following randomization, one group received 12.5 μg misoprostol sublingually and a vaginal placebo, while the other group received a sublingual placebo and 25 μg misoprostol vaginally. The primary outcome was the frequency of tachysystole. Student's t-test, the chi-square test of association and Fisher's exact test were used, as appropriate. Risk ratios and their 95% confidence intervals were calculated. Results The frequency of tachysystole was lower in the group using 12.5 μg misoprostol sublingually compared to the group using 25 μg misoprostol vaginally (RR = 0.15; 95%CI: 0.02-0.97; p = 0.002). Failure to achieve vaginal delivery within 12 and 24 h was similar in both groups. Sublingual administration was preferred to vaginal administration by women in both groups; however, the difference was not statistically significant. Conclusion The effectiveness of labor induction with low-dose sublingual misoprostol was similar to that achieved with vaginal administration of the recommended dose; however, the rate of tachysystole was lower in the sublingual group, and this route of administration may prove a safe alternative. Trial registration Registration number: NCT01406392, ClinicalTrials.gov. Date of registration: August 1, 2011.